Green shipping in the maritime industry : the prospect of LNG as marine fuel - Zhou, Xuan (2015)
There is an urgent need for ships to control their emissions, even when shipping is considered to be the most eco-friendly means of transportation. According to IMO‘s MARPOL Convention Annex VI, the sulphur content in HFO needs to be less than 3.5% effective 1 January 2012 and will decrease in the subsequent years down to below 0.5%. On the SECA areas from 1st January 2015, the sulphur ratio in marine fuels needs to be less than 0.1%. The lowered emission cap increases the bottom line cost of companies and significantly escalate the demand for alternate fuels. Liquefied natural gas (LNG) serves as an attractive alternative for ships to meet the impending stricter emission limit enforced by IMO, in particular affecting the Emission Control Areas (ECA map is included as Annex 1). Part of the primary motivations to use LNG is its promising environmental sustainability. Heightened regulation in pursuing better fuel quality and reduced emission of sulphur oxides (SOx), nitrogen oxides (NOx), and particulate matters (PM), has prompted the advancement of more sophisticated ship engine, and post-treatment technique for the ordinary residual-fuelled and distillate-fuelled vessels. In addition, using LNG as marine fuel is proven to be technically feasible and safe. There has been a sterling track record in terms of safety for the onloading/offloading of ships, and for operating the propulsion system fuelled by boil-off gas. Furthermore, Norwegian companies have a decade of experience operating on small vessels using LNG-fuelled propulsion. The main concern making the end-users reluctant to switch to LNG is the financial and economic feasibility of using LNG as marine fuel. Both retrofitting of vessels by installing the LNG system and building new LNG-fuelled vessel require a large sum of capital investment with unclear payback time and return on investment estimate. The fluctuation in the global oil price adds uncertainty to the conventional bunker prices and LNG hub prices. Moreover, it is observed that a general absence of bunkering infrastructure in seaports presents a major obstacle preventing the breakthrough of LNG as a ship fuel. At the early development stage, LNG marine fuel price is subject to additional logistic and distribution costs due to the inadequate infrastructure of small scale LNG supply system, and this additional costs vary to a large extent for suppliers in different locations depending on the cost efficiency of the supply value chain. 5 The infrastructure development for small scale LNG supply at the current stage still relies on governmental support. Hence the role of government is important in facilitating and promoting LNG as a marine fuel (S. Wang, T Notteboom 2014). Government agencies can deploy various financial tools to help the development of LNG value chain infrastructures, thus help to ensure the access to the LNG supply and reduce the logistics and distribution costs of LNG fuel. Moreover, the government can play a proactive role in encouraging ship conversions and promoting LNG as marine fuel by tax incentive provisions, direct subsidies, and funding to ship owners - all in a way to alleviate the financial burden of ship owners to switch to LNG.